A Scoping Review Study to Identify the Effects of Parenting on Development of Grit During Adolescence - Rika Hardani; Diana Setiyawati (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
Introduction: Grit defines as being passion and perseverance applied to achieve targets in the long term. The purpose of this scoping review is to investigate the extent and nature of research activities around the effects of parenting on adolescent grit. The purpose of this scoping review is to investigate the extent and nature of research activities around the effects of parenting on adolescent grit. Methods: We conducted a scoping review to understand the influence of parenting on adolescent grit development, based on Arksey and O'Malley's framework. We searched from 6 search database systems (ProQuest, EBSCO, Google Scholar, Science Direct, Scopus and JSTOR tracked since 2007-2020). The total number of participants in the selected article was 8,136 participants, with details of 7736 adolescents and 400 parents. Included sources are written in eight different countries (United States, China, Italy, Hong Kong, Taiwan, Japan, UK and Australia). Results & Conclusion: The results of this scoping review indicate that parenting has an important effect on adolescent grit development. Positive parenting will affect the building of high grit and negative parenting will reduce grit levels in adolescents. However, one study in China found that negative parenting behavior creates high grit in adolescents. The results of the scoping review are expected to be used as a basis for developing grit research in the family sector. It is also hoped that it can be used as a guide for planning programs for parents for the development of adolescent grit.